Learning Nursing Ethics - Experience of Students of Dhaka Nursing College, Bangladesh - ASM, Nurunnabi (Community Based Medical Journal, 2019)
Nursing ethics is taught in the subject 'Fundamentals of Nursing' in BSc Nursing curriculum in Bangladesh. The present study aims to examine nurse students' opinion regarding their learning nursing ethics. A total of 183 nursing students of Dhaka Nursing College, Bangladesh, from 1st year and 2nd year of BSc in Nursing course participated in this study, which was done between July and September, 2011. A semi-structured questionnaire was given to them. Besides mentioning their age, sex, socio-economic status, the students were asked to provide information about their acquisition and application of knowledge on codes of ethics and an evaluation on faculties (23 items). Most of the students were from low socio-economic condition (n=157, 85.79%). Nursing students perceived that their educators' teaching of the statements of the codes was fairly extensive (ranged from 3.32±0.365 to 3.59±0.923). The highest scores dealt with the nurse-patient relationship, and the mission of nurses. Single items with highest scores highlighted confidentiality, alleviation of suffering, impartiality, support to patients and patients' family members, personal responsibility of her/his work and the quality of care as well as respect to human dignity and autonomy. The least taught statements concerned nurses and society and nursing as a profession. Single items with lowest scores dealt with nurses' professional competence, nurses' participation in discussion and decision-making. Students regarded their own knowledge of the code of ethics (3.45±0.585) and their skills to apply in practice (3.51±0.573) as average. Two-thirds of students (n=122; 66.67%) assessed their educators' knowledge as fully or almost adequate to teach, 15.85% (n=29) of the students assessed the knowledge as less adequate, and 17.48% (n=32) could not assess it. Studying nursing students' opinions on learning nursing ethics would be a useful guide for the formation of their professional role as well as their education and training. CBMJ 2019 January: vol. 08 no. 01 P: 30-34